Lack of GNAS re-methylation during oogenesis may be a cause of sporadic pseudohypoparathyroidism type Ib (PHP1B) - DEMİRCİOĞLU, SERAP (My University, 2021)
CONTEXT: Pseudohypoparathyroidism type Ib (PHP1B) is characterized by hypocalcemia and hyperphosphatemia due to PTH-resistance in the proximal renal tubules. Maternal pathogenic STX16/GNAS variants leading to maternal epigenetic GNAS changes impair expression of the stimulatory G protein alpha-subunit (Gsα) thereby causing autosomal dominant PHP1B (AD-PHP1B). In contrast, genetic defects responsible for sporadic PHP1B (sporPHP1B) remain mostly unknown. OBJECTIVE: Determine whether PHP1B encountered after in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) causes GNAS re-methylation defects similar to those in sporPHP1B. DESIGN: Retrospective analysis. RESULTS: Nine among thirty-six sporPHP1B patients investigated since 2000, all with LOM at the three maternal GNAS DMRs and gain-of-methylation (GOM) at the paternal NESP DMR, had been conceived through IVF or ICSI. Besides abnormal GNAS methylation, IVF/ICSI-PHP1B cases revealed no additional imprinting defects. Three of these PHP1B patients have dizygotic twins and four have IVF/ICSI-conceived siblings, all with normal GNAS methylation; two unaffected younger siblings were conceived naturally. CONCLUSION: Sporadic and IVF/ICSI-conceived PHP1B patients revealed indistinguishable epigenetic changes at all four GNAS DMRs thus suggesting a similar underlying disease mechanism. Given that re-methylation at the three maternal DMRs occurs during oogenesis, male factors are unlikely to cause LOM post-fertilization. Instead, at least some of the sporPHP1B variants could be caused by a defect(s) in an oocyte-expressed gene that is required for fertility and for re-establishing maternal GNAS methylation imprints. It remains uncertain, however, whether lack of GNAS re-methylation alone impairs oocyte maturation because of insufficient Gsα expression, thus necessitating Assisted Reproductive Technology (ART) for conception.
Keywords: epigenetics; PTH; calcium; GNAS methylation; Gs-alpha; Gsα; in vitro fertilization (IVF); intracytoplasmic sperm injection (ICSI); phosphate; pseudohypoparathyroidism type Ib (PHP1B); STX16-GNAS